A STUDY ON THE STUDENTS’ PERCEPTION OF UTILIZING WHATSAPP AS A TOOL OF TEACHING LISTENING TO ASSIST DISTANCE LANGUAGE LEARNING - Fitria Wulan Sari (FKIP Universitas Khairun, 2021)
Listening is one of the skills in English which should be mastered well by the person who learns it. As the foreign language, it is not easy for the Indonesian students to master this skill. Moreover during the lockdown period of Covid-19 epoch when the students have distance language learning as the government policy, the process of teaching and learning especially teaching listening becomes more difficult. The use of tool is so important to support the process of teaching and learning in this situation. WhatsApp is chosen as the tool in the process of teaching and learning. This study aims to explore the English undergraduate students’ perception of the utilizing WhatsApp as a tool of teaching listening to assist distance language learning. The data were analyzed using questionnaire and interview. After analyzing the data, the research findings show that students have positive perception towards the use of WhatsApp for learning listening. It is an easy, fun, pleasant and good tool to use in the teaching learning process. It makes the students enthusiasm to learn and can help them to get the listening audio material which they must listen easily.